2011
DOI: 10.1002/jsfa.4578
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of lactic acid bacteria in sian‐sianzih (fermented clams), a traditional fermented food in Taiwan

Abstract: The results demonstrate that various LAB species are distributed in sian-sianzih and have a great effect on the flavor of sian-sianzih.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Besides L. garvieae E‐9 and E‐10, another three L. garvieae strains, which were previously isolated from wild clams (Chen et al . ), fermented clams (Chen et al . ) and fermented ginger (Chang et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides L. garvieae E‐9 and E‐10, another three L. garvieae strains, which were previously isolated from wild clams (Chen et al . ), fermented clams (Chen et al . ) and fermented ginger (Chang et al .…”
Section: Resultsmentioning
confidence: 99%
“…), fermented clams (Chen et al . ) and fermented ginger (Chang et al . ), were also used as indicator strains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, we reported that W. hellenica 4-7, isolated from fermented clams (sian-sianzih), is capable of producing a bacteriocin-like inhibitory substance (BLIS) (Chen et al 2012). However, the primary structure and biochemical characteristics of the BLIS from W. hellenica 4-7 have not yet been discussed.…”
Section: Introductionmentioning
confidence: 99%